PEMBERIAN MOTIVASI TERHADAP KARYAWAN YANG TERDAMPAK PHK PT, SUMBIRI DAN STAR VISION LEWAT PEMBAGIAN SEMBAKO DI KEC. BAWEN KAB SEMARANG - Samtono; TriMaryani (Jurnal Pengabdian Masyarakat Waradin, 2022)
Many cases of this mysterious pneumonia infection are indeed found in these animal markets. The Corona virus or COVID-19 is thought to be carried by bats and other animals that are eaten by humans until transmission occurs. Coronavirus is actually no stranger to the world of animal health, but only a few types are capable of infecting humans and causing pneumonia. Before the COVID-19 outbreak, the world was excited about SARS and MERS, which are also related to the Corona virus. With this background, the Corona virus is not only this time making citizens of the world panic. Having the same flu-like symptoms, the Corona virus develops rapidly, resulting in more severe infections and organ failure.